WHO BEARS THE BURDEN? GENDER, CONTRACEPTIVE RESPONSIBILITY, AND THE LEGAL REGULATION OF REPRODUCTIVE CHOICE IN INDONESIA - Heni Widiyani; Nikodemus Niko; Merlin Swantamalo Magna; Ayu Efritadewi (Jurnal Hukum Progresif, 2026)
This study examines how gender relations, cultural norms, religious beliefs, and state intervention shape contraceptive responsibility and reproductive choice in Indonesia. It focuses on gender imbalance in family planning, in which women bear the social and moral burden of contraception, while men remain marginally involved. Drawing on socio-legal analysis, feminist theory, and Michel Foucault’s concept of biopower, the study analyses legislation, policy debates, historical developments, and scholarship, with particular attention to Government Regulation No. 28 of 2024 and recent controversies concerning contraceptive access and vasectomy. The findings show that contraception in Indonesia is not merely a matter of medical choice, but a contested field structured by patriarchy, religious interpretation, cultural expectations, healthcare systems, and population policy. Women’s reproductive decisions are frequently influenced by husbands, medical authorities, and state programmes, while male contraceptive participation remains limited by narrow method availability and dominant ideals of masculinity. The regulation of adolescent access to contraception further reveals tensions between reproductive health, moral governance, abstinence, and cultural values. Through a biopolitical lens, family planning emerges as both a public health instrument and a mechanism for managing population, productivity, and social order. The study argues that reproductive autonomy cannot be realised through expanded contraceptive availability alone. Effective reform requires gender-responsive policies that promote meaningful male participation, safeguard informed and voluntary choice, address coercive and patriarchal decision-making, and recognise Indonesia’s diverse social, religious, and cultural contexts. Responsibility for contraception must therefore be understood as shared, negotiated, and grounded in individual rights rather than assigned predominantly to women.